Rice Price Prediction System Based on Rice Quality and Milling Level using Multilayer Perceptron - Nur Nafi'iyah; Muchammad Khudori (Jurnal Informatika Universitas Pamulang, 2022)
Bacpropagation algorithm is a neural network algorithm that has good performance. In addition to Backpropagation, SVM also includes a neural network algorithm. SVM also has a good performance in making predictions. This is based on previous research related to rice price predictions. During the COVID-19 pandemic, the government is obliged to maintain the stability of the price of basic necessities or basic commodities, the reason is to maintain the availability of basic commodities. Based on the conditions in the field, this research will create a rice price prediction system based on the type of rice quality at the milling level. The purpose of this research is to help stabilize rice prices in the market. The method used to predict is Backpropagation by proposing 2 architectures, namely 3-25-1, and 3-35-1. The dataset used is taken from bps.go.id, the total dataset is 318, and the method of evaluating the prediction results is using the MAE value. Based on the trial the lowest MAE value is 305.93 in the first architecture 3-25-1.